The efficacy and effectiveness of enterovirus A71 vaccines against hand, foot, and mouth disease: A systematic review and meta-analysis. - Xuemei Yan; Yuanhua Liu; Fengkun Chen; Zhaorui Chang; Zhijie Zhang; Margarita Pons-Salort; Nicholas C Grassly (PLoS ONE)
Enterovirus A71 (EV-A71) is a major cause of severe hand, foot, and mouth disease (HFMD) among children in the Asia-Pacific region. Here we review randomised clinical trial data and post-licensure effectiveness studies of inactivated EV-A71 vaccines following their development and licensure in China since late 2015. We searched PubMed, Web of Science Core Collection, Elsevier ScienceDirect, China National Knowledge Infrastructure (CNKI), and Wanfang Data on 20 May 2024 with no date restriction in English and Mandarin, using key terms including "EV-A71", "enterovirus 71", "hand, foot, and mouth disease", "HFMD", "vaccine", "efficacy", "effectiveness", "protection" and "impact". Phase III randomized controlled trials (RCTs) reporting vaccine efficacy and observational studies on effectiveness were eligible for inclusion. We excluded studies that evaluated non-laboratory confirmed HFMD associated outcomes, abstracts, reviews, comments, animal studies, cross-sectional studies, and modelling studies. Summary measures of vaccine efficacy and effectiveness were based on random-effects models. After screening, 14 articles were eligible for inclusion, including 6 reporting 4 different phase III RCTs. Estimated efficacy of 2 doses of EV-A71 vaccine against EV-A71 associated HFMD 1 year after vaccination ranged from 90.0% to 97.9%, with an overall estimate for all products of 95.6% (95% Confidence Interval: 92.1, 97.5). Efficacy remained high at 26 months post-vaccination, ranging from 94.7% to 94.8%. The estimated overall effectiveness of 2-dose vaccination against any EV-A71-HFMD across five test-negative case-control studies was 84.3% (95% CI: 75.2, 90.0) among children aged 0-12 years. Effectiveness was higher in older children compared to younger children (85.3% (72.9, 92.1) vs. 79.8% (61.2, 89.5)) and higher against severe compared with non-severe EV-A71-HFMD (90.0% (80.0, 95.0) vs. 76.5% (50.0, 89.0)). The effectiveness declined in more recent studies with longer follow-up. Inactivated EV-A71 vaccines offer a high level of protection against EV-A71 HFMD. Longer term studies are needed to evaluate the persistence of protection beyond 2 years post-vaccination.